Research on Bearing Theory of Squeezed Branch Pile. (29th December 2020) - Ma, Hong-wei; Wu, Yi-ying; Tong, Yu; Jiang, Xiao-qiang
Abstract : Based on the shear displacement method, theoretical research on the load transfer relation of squeezed branch pile is established. In combination with the nonlinear relation of the interaction between piles and soil, the hyperbolic function is used to describe the pile tip, pile skin, and branch. The theoretical method of the load transfer is improved, and the expression of the load transfer coefficient of these three parts is given. Finally, the applicability of the theoretical method is verified by the model test of homogeneous soil and the field test of stratified soil. The verification results show that the theoretical calculation method of the squeezed branch single-pile bearing capacity based on the shear displacement method can better calculate the ultimate load in practical engineering applications.